Development and validation of a competence model for educational researcher in the Mongolian context - Itgel Miyejav; Khajidmaa Otgonbaatar; Purev Ochir (Institute of Advanced Engineering and Science, 2023)
In the 21st century, competences of educational researchers become increasingly complex and highly significant. Although various discussions and competencies have been for researchers in general, no frameworks have been devised specifically for educational researchers. This study aimed to establish a competence model for educational researcher (CMfER). The dimensions and items were created from a conceptual analysis of the literature, in-depth interviews, and focus interviews. Eight experts in the field of educational research evaluated the content validity. The reliability and validity of the CMfER were examined utilizing a sample of 240 Mongolian educational researchers. The 24-item four factor model was validated using confirmatory factor analysis (CFA), and the results showed adequate model fits. The factor loadings of the model were substantially significant, and Cronbach’s alpha coefficient was well above the threshold value, suggesting that the items were internally consistent and reliable. Overall, the results shown that the CMfER can be used as a reliable and valid data collection tool in future studies in which educational researchers’ competences are examined.